Analysis of Local Community Ecological Knowledge on Mangrove Ecotourism Development in Talaga Yenelo, Sagea Village, North Weda District Central Halmahera District - Fabanjo, M. Aban; Abdullah, Nursanti; Ahmad, M. Ali (Jurnal Biologi Tropis, 2024)
Local ecological knowledge is knowledge and beliefs that are largely derived from observations of the ecological processes of resources in the surrounding area and the various factors that influence them based on the logical interpretation of local communities. Local ecological knowledge has an important role in informing sound spatial, spatial and temporal management approaches for marine spatial planning. The aim of this research is to identify the ecological knowledge of local communities regarding the mangrove ecosystem and 2) Community perceptions regarding the management of mangrove ecotourism in Talaga Yenelo in Sagea Village and 3). The level of perception of local communities regarding Ecotourism activities. The method used in this research is determining the sample in this research using a purposive sampling method, namely respondents who participate are deliberately selected by researchers according to the criteria of research respondents. To determine people's knowledge and perceptions, it is based on a Likert scale assessment system and multiple linear regression analysis to see the influence of several independent variables on one dependent variable. The research results show that the people of Sagea and Kiya villages have better knowledge of the local ecology of mangrove forests, especially mangrove habitat, factors of mangrove damage and the impact of mangrove damage compared to the function of mangroves. with the level of utilization of the mangrove ecosystem in the villages of Sagea and Kiya varying greatly. While understanding of mangrove ecotourism activities is very minimal, they agree with the ecotourism activities carried out. Therefore, there is a need for follow-up action from the government regarding mangrove forest management based on the mangrove forest environment.